Manifestation of Axiological and Motivational Aspects in E-Learning Products - Dumčienė, A.; Sipavičienė, S. (Elektronika ir Elektrotechnika, 2010)
The objective of the present paper is to explore and evaluate the quality of e-learning courses in terms of their promotion of value attitudes and motivation development. The evaluation was conducted by applying thirteen group criteria. The difference between the evaluations of the experts and students it is not statistically significant (p> 0.05). This result helps to draw together the attitudes of the instructors as well as those preparing the products of e-learning and users, i.e. students; this enables to improve the product quality.